Small non-coding RNAs as determinants of viral replication - Salvador, Rafaela Alexandra Massa (2022)
Influenza A virus (IAV) is a respiratory virus in constant circulation throughout the world, causing annual epidemics and resulting in millions of deaths. IAV proteins interact with numerous host cellular proteins and hijacks the host cellular machinery for virus replication and translation. Recently, several lines of evidence demonstrated that small non-coding RNAs (sncRNAs), such as microRNAs (miRNAs) and transfer RNA derived-small RNA (tsRNAs), were affected by viral infections. In fact, it has been shown that sncRNAs expression can change in response to viral infections, indicating that these molecules might play important roles in modulating viral infections using different mechanisms. However, their relevance for viral replication or host antiviral responses are still not clear. As such, with this project, we aimed to study the role of sncRNAs in IAV infection and unravel their relevance as putative therapeutic targets. To that end, we traced the profile of sncRNAs during viral infection by Next Generation small-RNA sequencing. We identified several deregulated miRNAs during IAV infection that putatively target genes involved in the immune response. Concerning the tsRNA profile, most of the tsRNAs identified were tRNA-derived fragments (tRFs) that were formed upon IAV infection. Our data suggests that sncRNAs can have a crucial role in viral infection, however further studies need to be performed to understand how they regulate infection. Furthermore, the role of two tRFs (5’ tRF-GLU-CTC and 5’ tRF-GLU-TTC) in viral replication was tested, and we found that their abundance impairs IAV replication. Ultimately, we believe that understanding the effects of sncRNAs and their targets during IAV infection will enable the discovery of new antiviral therapeutic strategies.